Understanding the results of 14th Malaysian general election through Islamic perspectives: a new challenge in Islamizing political understanding - Saahar @Saabar, Suhaimee; Ahmad Dahlan, Mat Nadzari; Idid, Syed Arabi (Penerbit Universiti Sultan Zainal Abidin, 2020)
The results of the 14th General Election shocked many parties, especially the Barisan Nasional, which has dominated Malaysian politics for more than 60 years. Various studies and discoveries have been made to understand the context of this defeat from various angles of thinking and understanding. However, in the study of Malaysian politics Islamic perspective is also taken into account to balance the understanding between Western and Islamic understanding. Scholars have long used Western thought to explain political phenomena and how power is used in maintaining a political party. The purpose of this paper is to explain in detail the results of elections from an Islamic perspective. This is to differentiate the views given by Western thinkers and to provide a new framework based on the Islamic perspective taking into account the values and teachings of Islam itself. Therefore, this paper seeks to provide a different perspective on how new explorations can be translated into the context of political studies in the country.